The Role of Dopant Concentration on Conductivity and Mobility of CdTe Thin Films - Ala J. Al-Douri; F. Y. Al-Shakily; Abdalla A. Alnajjar; Maysoon F. A. Alias (Advances in Condensed Matter Physics)
Films of CdTe pure and doped with various atomic percentages of Al and Sb (0.5, 1.5 & 2.5) were prepared, and their electrical properties were investigated. The films were prepared by thermal evaporation on glass substrates at two substrate temperatures (Ts=RT & 423 K). The results showed that the conduction phenomena of all the investigated CdTe thin films on glass substrates are caused by two distinct mechanisms. Room temperature DC conductivity increases by a factor of four for undoped CdTe thin films as Ts increases and by 1-2 orders of magnitude with increasing dopant percentage of Al and Sb. In general, films doped with Sb are more efficient than Al-doped films. The activation energy (Ea2) decreases with increasing Ts and dopant percentage for both Al and Sb. Undoped CdTe films deposited at RT are p-type convert to n-type with increasing Ts and upon doping with Al at more than 0.5%. The carrier concentration decreases as Ts increases while it increases with increasing dopant percentage. Hall mobility decreases more than three times as Al increases whereas it increases about one order of magnitude with increasing Sb percentage in CdTe thin films deposited at 423 K and RT, respectively.